Deprivation in New Zealand: Regional Patterns and Changes - David C Mare; Peter Mawson; Jason Timmins (New Zealand Government, The Treasury, 2001)
This paper presents an analysis of the distribution of socio- economic deprivation throughout New Zealand. The analysis focuses on the three census years 1986, 1991, and 1996. A summary deprivation measure is constructed which approximates New ZealandDep96 using standard regression techniques. The paper extends a static analysis of deprivation by examining changes to the deprivation profile across time on a regional basis. Differences in the incidence of deprivation for different ethnic groups are emphasised. Maori and Pacific people are more likely to live in deprived meshblocks than their European counterparts. We also touch on the role isolation plays in determining the distribution of deprivation.
Keywords: I30; R10; 330; deprivation; inequality; distribution; meshblocks; regions